Risk factors and effect of selective removal on retroviral infections prevalence in Belgian stray cats. (9th January 2016) - Garigliany, M.; Jolly, S.; Dive, M.; Bayrou, C.; Berthemin, S.; Robin, P.; Godenir, R.; Petry, J.; Dahout, S.; Cassart, D.; Thiry, E.; Desmecht, D.; et al.
Abstract : The aim of this study was to evaluate the effect of several risk/protective factors and predictors on the prevalence of feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) infections in 302 stray cats captured during a trap‐neuter‐release programme in a mixed urban‐rural area from Belgium, from 2010 to 2012. The impact of selective removal of FIV‐positive cats on the apparent prevalence in the remaining population over this three‐year period was also assessed. The seroprevalences over three years were 18.8 per cent for FIV and 0.7 per cent for FeLV. For FIV, the seroprevalence decreased significantly from the first year of the programme (2010; 30.5 per cent) to the last (2012; 13.1 per cent). Sex (male) and age (adult and old cats) were risk factors, while the year of sampling (years 2011 and 2012) was a protective factor. Age, sex and location were the most relevant predictors of FIV status. The data presented in this study revealed a very high FIV seroprevalence in Belgian stray cats, while FeLV was almost absent. The selective removal of positive cats had a drastic effect on the FIV seroprevalence in the remaining cat population.